The burden of systemic sclerosis in Switzerland – the Swiss systemic sclerosis EUSTAR cohort (Swiss Medical Weekly, 2021)
OBJECTIVES Characteristics of Swiss patients with systemic sclerosis have not been described so far. The aim of the current study was to identify unmet needs in comparison with other European countries that could inform specific interventions to improve the care of systemic sclerosis patients. METHODS We analysed Swiss and other European systemic sclerosis patients registered in European Scleroderma Trials And Research (EUSTAR) and the Very Early Diagnosis Of Systemic Sclerosis (VEDOSS) cohort. Demographics, clinical profiles, organ involvement and survival of established, early/mild and very early / very mild systemic sclerosis patients were described and compared between the cohorts. RESULTS We included 679 Swiss and 8793 European systemic sclerosis patients in the analysis. Over 95% of patients in both cohorts were Caucasian, disease subsets were similar, and no age difference was found. The Swiss cohort had more male patients (25% vs 16% European, p = 0.005) and higher prevalence of early/mild and very early / very mild patients (26.1 vs 8.5% European and 14.9% vs 6.7% European, respectively, both p